Gerakan Sosial Masyarakat Tegal Binangun Kabupaten Banyuasin Provinsi Sumatera Selatan - Akta Dwi Putra; Norhuda Norhuda; Ryllian Chandra (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
The title of this research is "Tegal Binangun Community Social Movement Banyuasin Regency, South Sumatra Province". This movement is in order to maintain their administrative status from the demands of recognition of the Banyuasin District Government based on Law Number 23 of 1988 concerning Changes to the Regional Levels of the Palembang Second Level Region, Musi Banyuasin District Level II District and Ogan Komering Ilir Level II District. The purpose of this study was to determine the dynamics and patterns used by the community movement so that the demands and resistance of the Tegal Binangun community were realized by the Government of the Province of South Sumatra and Banyuasin District. The method used in this research is a qualitative research method with a case study approach with stages, namely interviews, observation, and documentation. Meanwhile, the source of this research is primary data sources. Based on the results of the study it can be seen that, this movement carried out resistance against the Banyuasin District Government, ranging from peaceful actions to delivering letters to the DPRD of South Sumatra Province, the Governor of South Sumatra, the President, the DPR-RI, the Minister of Youth and Sports, the Minister of Home Affairs, and Mayor of Palembang. The researcher uses the theory from Sidney Tarrow that is in line with this conflict that a group of people or ordinary citizens who join and form an alliance with figures or groups that have a large influence in a country, groups or the like move together to make a fight against the holders of power or the political elite if what is considered to be a policy is not in accordance with what is desired. Until now, when the Banyuasin District Government put pressure on the community, immediately the Tegal Binangun community took the fight. This conflict has not found a solution because it is still being resolved by the Government of South Sumatra Province. In this study it was found that the social movement of the Tegal Binangun community was formed to carry out resistance to the Banyuasin District Government's unilateral recognition of the Tegal Binangun area.